Pengaruh Sistem Marketing Bank Syariah Terhadap Preferensi Dan Permintaan Masyarakat - Muhammad Fadhil Junery (LPPM ISNJ Bengkalis, 2014)
Marketing strategy is not just limited to meet the customer but also a lot of rethinking and changing what is perceived by the customer, so the creation of customer preferences for products or services offered. The first objective of this study is to investigate and analyze the influence of the dimensions of price, products, services and processes directly or indirectly to the preferences of the Islamic Bank. The second objective of this study is to investigate and analyze the influence of the dimensions of price, product, service, and process the request through the client's preferences at the Islamic Bank. This study uses a quantitative approach that intends to explain causal relationships between variables through hypothesis testing. In these study methods of data analysis using path analysis (path analysis). The results of path analysis showed that the first sub-dimensional structure of pricing, product, process and especially the dimension of service capable of providing significant direct influence and positive impact on customer preference in Islamic Bank. The second sub-structure shows that the dimensions of price, product, service and process indirect significant effect on customer demand through customer preference in Islamic Banks. The results of this analysis also indicate that customer preference is a mediating variable in creating and enhancing customer demand at the Islamic Bank.